2009
DOI: 10.1111/j.1399-0004.2009.01284.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of CYP1B1 mutations and association of heterozygous hypomorphic alleles with primary open‐angle glaucoma

Abstract: Glaucoma is an inherited complex and heterogeneous disease, and one of the most prevalent causes of definitive blindness in the world. Recent reports have indicated that heterozygous mutations of the CYTOCHOROME P4501B1 (CYP1B1) gene are present in 4-10% of patients with primary open-angle glaucoma (POAG). To further evaluate the role of CYP1B1 mutations in POAG we extended our previous association study and carried out a functional analysis of the mutations identified by polymerase chain reaction (PCR) DNA se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 15 publications
1
29
0
1
Order By: Relevance
“…Recent studies have reported conflicting results regarding the relationship between the occurrence of POAG and mutations in the CYP1B1 gene. Several studies have reported that POAG patients express only mutated CYP1B1 (Melki et al, 2004;Lopez-Garrido et al, 2006;Chakrabarti et al, 2007;Kumar et al, 2007;Suri et al, 2008;Hilal et al, 2010;Lopez-Garrido et al, 2010;Milla et al, 2013;Zhou et al, 2013). Some studies have also observed an association between single nucleotide polymorphisms (SNPs) in the CYP1B1 gene and POAG incidence (Melki et al, 2005;Acharya et al, 2006;Bhattacharjee et al, 2008;Burdon et al, 2010;Fan et al, 2010;Patel et al, 2012;Buentello-Volante et al, 2013;Gong et al, 2015;Micheal et al, 2015;Williams et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported conflicting results regarding the relationship between the occurrence of POAG and mutations in the CYP1B1 gene. Several studies have reported that POAG patients express only mutated CYP1B1 (Melki et al, 2004;Lopez-Garrido et al, 2006;Chakrabarti et al, 2007;Kumar et al, 2007;Suri et al, 2008;Hilal et al, 2010;Lopez-Garrido et al, 2010;Milla et al, 2013;Zhou et al, 2013). Some studies have also observed an association between single nucleotide polymorphisms (SNPs) in the CYP1B1 gene and POAG incidence (Melki et al, 2005;Acharya et al, 2006;Bhattacharjee et al, 2008;Burdon et al, 2010;Fan et al, 2010;Patel et al, 2012;Buentello-Volante et al, 2013;Gong et al, 2015;Micheal et al, 2015;Williams et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, PCG would be attributable to a severe deficiency in the activity of the enzyme, and juvenile glaucoma or primary open-angle glaucoma would be the outcome of a moderate or mild enzyme deficiency, respectively. 4,8 Finally, the benefits of genetic studies addressing PCG are undeniable as they allow for an early diagnosis and genetic counseling. Notwithstanding, PCG is still considered poorly predictable.…”
Section: Discussionmentioning
confidence: 99%
“…17 These factors need to be considered in genetic counseling. 8 Several studies have also tried to correlate the way in which PCG presents with the existing CYP1B1 mutation. Thus, a more severe disease, especially in homozygotes, and an earlier onset age along with a need for more surgical procedures have been observed in patients with mutations in this gene.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Our early observations of lack of clinical manifestations in CYP1B1/LTBP2 double carriers may be attributed to the involvement of the two genes in independent pathways of eye development and glaucoma pathogenesis. However, it is important to note that both CYP1B1 variantsp.E229K and p.R368H -lead to reduced, not abolished, enzyme activity and protein stability, 40,41 and display incomplete penetrance. 42,43 CYP1B1-LTBP2 interactions and their clinical implications need to be addressed in larger samples of double carriers of wellsupported pathogenic mutations.…”
Section: Population Genetics Of Pcg In Gypsiesmentioning
confidence: 99%